E-learning and games for training, education, health and sports 7th International Conference, Edutainment 2012 and 3rd International Conference, GameDays 2012, Darmstadt, Germany, September 18-20, 2012. Proceedings - Göbel, Stefan (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 7th International Conference on E-Learning and Games, Edutainment 2012, held in conjunction with the 3rd International Conference on Serious Games for Training, Education, Health and Sports, GameDays 2012, held in Darmstadt, Germany, in September 2012. The 21 full papers presented were carefully reviewed and selected for inclusion in this book. They are organized in topical sections named: game-based training; game-based teaching and learning; emerging learning and gaming technologies; authoring tools and mechanisms; and serious games for health.